The coming Balkan caliphate the threat of radical Islam to Europe and the West - Deliso, Christopher (Praeger Security International, 2007)
With all eyes currently focused on the widening conflict in the Middle East and the terrorist threat coming from the region, the West is in danger of overlooking a potent new battleground in the greater "war on terror"--the Balkans. This historically volatile region saw some of the worst violence of the late 20th century in the Yugoslav Wars of Secession. During these conflicts, stunningly shortsighted and politically motivated policies of the United States and its allies directly allowed Islamic mujahedin and terrorist-related entities to establish a foothold in the region--just as with the progenitors of the Taliban a decade earlier in Afghanistan. Although the 9/11 attacks caused a partial reassessment of Western policy, it may already be too late for a region still largely ignored. The proliferation of foreign fundamentalist groups has had a cancerous effect on traditional Balkan Islamic communities, challenging their legitimacy in unprecedented and often violent ways
Includes bibliographical references and index
Keywords: Geschichte; Terrorismus; Terrorism -- Balkan Peninsula; Islam -- Balkan Peninsula -- History; Islam and politics -- Balkan Peninsula; Radikalismus; Islam; Balkan Peninsula -- Ethnic relations; Balkanhalbinsel